Law and religion in Europe a comparative introduction - Doe, Norman (Oxford : Oxford University Press, 2011)
A comparative introduction for students on the national laws governing religion in Europe, this book examines national laws particularly as they affect the attitudes of states towards religion, religious freedom and discrimination, and the legal position and autonomy of religious organizations.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Religion and law -- European Union countries